Analysis of Polarization-Dependent Light Extraction and Effect of Passivation Layer for 230-nm AlGaN Nanowire Light-Emitting Diodes - Yu Kee Ooi; Cheng Liu; Jing Zhang (IEEE Photonics Journal, 2017)
This paper investigates the polarization-dependent light extraction efficiency ( $η _{\rm extraction}$ ) and the effect of passivation layer for AlGaN-based nanowire (NW) deep-ultraviolet (DUV) light-emitting diodes (LEDs) emitted at 230 nm using three-dimensional finite-difference time-domain method. Our results show that the use of NW structure for 230-nm LEDs can result in higher transverse-magnetic (TM) polarized $η _{\rm extraction}$ than transverse-electric (TE) polarized $η _{\rm extraction}$ . Specifically, $η _{\rm extraction}$ up to ∼48% for TM polarization and ∼41% for TE polarization can be achieved by the investigated 230-nm NW LEDs as compared to conventional planar LEDs (∼0.2% and ∼2% for TM- and TE-polarizations, respectively) attributed to the large surface-to-volume ratio and strong sidewall emissions. In addition, the analysis on the effect of various passivation layer materials suggests the use of SiO2, which has smaller refractive index than the NW core, could extract more photons out of the NW core and lead to TM-polarized $η _{\rm extraction}$ up to ∼47%. Therefore, the use of the AlGaN NW structure is expected to lead to high external quantum efficiency DUV LEDs due to the large TM-polarized $η _{\rm extraction}$ in combination with the dominant TM-polarized spontaneous emissions at 230 nm.